A declaration for all seasons: The IFLA Statement on Libraries and Intellectual Freedom. (October 2022) - Byrne, Alex
A quarter century after the momentous establishment of IFLA's Committee on Free Access to Information and Freedom of Expression is an appropriate time to reflect on the landmark IFLA Statement on Libraries and Intellectual Freedom. The Statement consciously broadened IFLA's remit, locating intellectual freedom as a fundamental human right and a core responsibility of the library profession that operates within libraries' commitments to diversity and plurality. As the examples discussed in this essay illustrate, the Statement continues to be relevant and is truly a declaration for all seasons. The concerns to be addressed encompass an extensive range of social justice concerns – concerns that are global and cover all elements of the library and information sector. Addressing those concerns and promoting intellectual freedom demands the intervention of trusted information agents to assist communities to use the Internet wisely and for the widest possible benefit. It demands the profession's concerted action, coupled with regular reporting and discussion in the library and information science literature. The profession has a challenging but vital role in preserving one of humanity's most precious rights: intellectual freedom.